High-performance photodetector arrays for near-infrared spectral sensing - Anne van Klinken; Don M. J. van Elst; Chenhui Li; Maurangelo Petruzzella; Kaylee D. Hakkel; Fang Ou; Francesco Pagliano; René van Veldhoven; Andrea Fiore (APL Photonics, 2023)
Spectral sensing is an emerging field driven by the need for fast and non-invasive methods for the chemical analysis of materials in agri-food, healthcare, and industrial applications. We demonstrate a near-infrared spectral sensor, based on a scalable fabrication process and combining high responsivity, narrow linewidth, and low noise. The sensor consists of 16 resonant-cavity-enhanced photodetectors, each showing a unique spectral response consisting of narrow peaks. The spectral sensor thereby covers the wavelength range between 890 and 1650 nm, where organic materials show relevant spectral features from first and second overtones. For the fabrication of the detector arrays, we propose a simple and scalable fabrication approach that yields largely improved device characteristics with respect to the grey-scale electron-beam lithography process reported earlier. Through a series of five optical lithography steps, tuning layers of silicon nitride are deposited stepwise to obtain 16 different thicknesses and reduced surface roughness. With this novel fabrication approach, the obtained photodetectors achieve an average peak linewidth of 55 nm, a maximum peak responsivity of 0.3 A/W, and high suppression of the non-resonant background. We also demonstrate the impact of these improvements on the sensing performance for two relevant problems through an experiment and a set of simulations. With lateral dimensions of ∼1.4 × 1.4 mm2, the proposed photodetector array can be the key to robust, portable, and low-cost sensing instrumentation for on-site material analysis in various application fields.